If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3xy + 3x + -2xy = 0 Reorder the terms: 3x + 3xy + -2xy = 0 Combine like terms: 3xy + -2xy = 1xy 3x + 1xy = 0 Solving 3x + 1xy = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'x'. x(3 + y) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(3 + y)' equal to zero and attempt to solve: Simplifying 3 + y = 0 Solving 3 + y = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + y = 0 + -3 y = 0 + -3 Combine like terms: 0 + -3 = -3 y = -3 Add '-1y' to each side of the equation. y + -1y = -3 + -1y Combine like terms: y + -1y = 0 0 = -3 + -1y Simplifying 0 = -3 + -1y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
x = {0}
| 9(a^2-4)+1=0 | | 7(47)-5y=34 | | 4+x=9-2 | | 100a^2-500a+600= | | 4x(x-3)+5x=48 | | 100a^2-500a-600= | | -4(2-y)+3y=(y-4) | | 2(2t+4)=0.75(24-8t) | | x-25+x+3(x-25)=275 | | a^2-21ab+110b^2=0 | | equation= | | 18-abs(7x+6)=6 | | -3x-1.9=-20.5 | | x(x-3)+5x=48 | | -.6x-.2=-.5+.5x | | 4x^2+25x^2=0 | | .625(6x+12)=5 | | 4x^2+25x^4=0 | | -x-17=-4+28 | | x+-12=24 | | 7x-5(59)=34 | | 6+3(z-2)=-6z+2 | | -2b+6b=-4 | | (4-7i)-(7-9i)= | | x-25+x+3x+22=275 | | 4*x^2+2*x=0 | | -c-3+1-9c+8-2c= | | x2+x6=2 | | 5(10-n)=-3n-10 | | 2+2x=7x-8 | | x^2-7xy+12y^2=0 | | x^2+15x+c= |